Ankle brachial pressure index to assess atherosclerotic risk in hypertensive subjects - Salagre, Santosh B.; Itolikar, Shobha M.; Chavan, Radhika J. (International Journal of Research in Medical Sciences, 2017)
Background: This research was planned to study correlation of ankle brachial pressure index (ABPI) with clinical features, laboratory investigations and anthropometric measurements in patients of essential hypertension and to establish association of atherosclerosis risk in hypertensive subject. Methods: This prospective observational year-long study was conducted after the institutional ethics committee approval in outpatient department of a tertiary care hospital. 153 adult non-pregnant patients were enrolled after written informed consent. Out of these, 51 patients each were of stage I hypertension, stage II hypertension and normal blood pressure. The ABPI were measured in the posterior tibial arteries using a Doppler ultrasound probe. The detailed demographic and anthropometric data was entered in proforma and data statistically analyzed. Results: In our study 28 (55%) out of 51 patients in stage II Hypertension had low ABPI as compared to 23 (45%) out of 51 patients in stage I Hypertension. No patients with normal blood pressure had low ABPI. There is significant correlation of stage of hypertension and ABPI (p <0.001). Mean ABPI (0.9102) in stage II hypertensive was low as compared to stage I hypertensive (0.9124) and normotensive subjects (1.0263). ABPI was inversely correlated with lipid profile. The hypertensive subjects with duration of hypertension for more than 5 years, the mean ABPI was significantly lower (0.8773) than those hypertensive subjects who had duration of hypertension less than 5 years (0.9526) (p 0.001). Conclusions: ABPI proves to be a non-invasive, bed side modality to assess the atherosclerotic risk in hypertensive patients.